Pengaruh Pendidikan Gizi terhadap Pengetahuan Ibu Tentang Stunting - Marlina, Titin; Rokhanawati, Dewi; Hidayat, Asri (IAI Nasional Laa Roiba Bogor, 2025)
Nutrition issues, particularly stunting, have become the focus of global attention due to their serious impact on children's health and development. Stunting, or chronic growth impairment, can have long-term consequences on children's physical and mental health, and even affect the productivity and well-being of society as a whole. In the midst of this complex challenge, the role of mothers as the primary caregiver and decision-maker when it comes to family diets is crucial. Therefore, it is important to evaluate and understand the effect of nutrition education on mothers' knowledge of stunting, in the hope of providing deeper insights to support stunting prevention efforts. This study aims to explore the effect of nutrition education on mothers' knowledge about stunting. This study employs a scoping review method with a systematic approach.